Application of ice-breaking activities for learning preparation for children aged 5-6 years at KB/RA Muslimat NU Darussalam Alastuwo - Rohana, Fida Beti; Setianingrum, Indah (ARKA INSTITUTE, 2025)
Children aged 5-6 years tend to have a short attention span, so special strategies are needed to build their learning readiness from the beginning of classroom activities. This study aims to determine the application of ice-breaking activities for learning preparation for children aged 5-6 years at KB/RA Muslimat NU Darussalam Alastuwo. The research method uses a qualitative descriptive approach. The subjects of the study were 20 children of Kindergarten B and 2 teachers. The results show that activities such as clapping games, interactive songs, and rhythmic movements are used to prepare children for learning before learning begins. However, the variation of activities is still limited, so it is necessary to develop more creative strategies. The recommendation of this study is that teachers can integrate ice-breaking activities inclusively and diversely in the daily curriculum.